Overlapping dimensions of autism spectrum disorder and attention-deficit/hyperactivity disorder - Castro, Carolina (2025)
This article provides a comprehensive review of the overlap between autism spectrum disorder and attention-deficit/hyperactivity disorder. It also examines the challenges that these overlaps pose in making accurate differential diagnoses and developing effective treatments.